ENERGУ PERFORMANCE OF PUBLIC BUILDINGS WITH REGARD TO THE THERMAL ENVIRONMENT ERGONOMICS - , Г. Г., О. І., М. В. (Municipal economy of cities. Series: «Economy science», 2017)
Energy consumption of buildings considerably depends on the premises’ microclimate criteria. Non-integrated approachto the thermal modernization of public buildings leads to deterioration of the premises’ microclimate. Temperature comfort is a state of being satisfied with the environment conditions. Human warm feeling is mainly connected with the body’s heat balance as a whole. Dependence of the heat balance upon the physical activity and clothes, as well as on the air temperature, mean irradiation temperature, movement velocity and air humidity is presented. At assessment or measurement of these factors it is possible to forecast the body’s warm feeling as a whole by means of the mean assessment calculation. Aspects of the thermal environment certification of premises have been studied based on the thermal comfort indices PMV-PPD. The necessity to include information on the building’s internal environment, as one of the parameters for assessing its overall energy performance, into the building’s energy certificate has been determined. While designing ther motechnical characteristics of the building’s thermal insulation sheeting elements, it is necessary to apply methods of forecasting the general warm feeling and the humans’ discomfort degree (thermal dissatisfaction), subjected to the impact of moderate thermal environment. .Keywords: ergonomics, indoor climate, thermal comfort.